2018
DOI: 10.1111/1751-7915.13263
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carbohydrate degradation pathways in Pseudomonas involves a versatile set of transcriptional regulators

Abstract: SummaryBacteria of the genus Pseudomonas are widespread in nature. In the last decades, members of this genus, especially Pseudomonas aeruginosa and Pseudomonas putida, have acquired great interest because of their interactions with higher organisms. Pseudomonas aeruginosa is an opportunistic pathogen that colonizes the lung of cystic fibrosis patients, while P. putida is a soil bacterium able to establish a positive interaction with the plant rhizosphere. Members of Pseudomonas genus have a robust metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 64 publications
5
43
0
Order By: Relevance
“…It has been reported to promote plant growth, prevent plant diseases, and can efficiently remove organic soil pollutants and environmental contaminants . P. putida features a versatile metabolism using the Entner–Doudoroff pathway for glucose catabolism, shows resistance against oxidative stress conditions, and genetic engineering tools are readily available . The carbohydrate substrate spectrum is limited and confined to hexoses , however, P. putida has been recently engineered to concomitantly consume xylose, cellobiose, and glucose, which are the basic building blocks of the abundant polysaccharides cellulose and hemicellulose .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to promote plant growth, prevent plant diseases, and can efficiently remove organic soil pollutants and environmental contaminants . P. putida features a versatile metabolism using the Entner–Doudoroff pathway for glucose catabolism, shows resistance against oxidative stress conditions, and genetic engineering tools are readily available . The carbohydrate substrate spectrum is limited and confined to hexoses , however, P. putida has been recently engineered to concomitantly consume xylose, cellobiose, and glucose, which are the basic building blocks of the abundant polysaccharides cellulose and hemicellulose .…”
Section: Introductionmentioning
confidence: 99%
“…carbon and nitrogen sources) and O 2 (Palmer et al, 2007;La Rosa et al, 2018) and bacterial cells often have to face other challenges simultaneously, such as the presence of multispecies microbiota and several types of stress factors, for example, immune responses, antibiotics and oxidative and osmotic stress (Moradali et al, 2017). Sophisticated regulatory networks in Pseudomonads control the physiological responses to these stressful conditions, including both local and global regulators that adjust transcriptional levels according to environmental cues (Tribelli et al, 2013;Balasubramanian et al, 2015;Arce-Rodríguez et al, 2016;Udaondo et al, 2018). Carbon catabolite repression, governed by the Crc protein, is a major player among these regulatory systems in Pseudomonas species (Wolff et al, 1991;Collier et al, 1996;Velázquez et al, 2004;Rojo, 2010;Grenga et al, 2017;Liu et al, 2017;Wirebrand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While our data suggest that aminoglycosides combined with C 4 -dicarboxylates might not be effective in killing P. aeruginosa isolates with RpoN loss of function, we have shown that two other carbon sources, ARG and GLC, can potentiate TOB killing of both wild-type and ΔrpoN antibiotic-tolerant cells. In P. aeruginosa, GLC diffuses across the outer membrane through the OprB porin into the periplasm (60,61). From there, GLC either is directly transported across the inner membrane via the Glt transporter or is converted to gluconate or 2-ketogluconate, which is transported into the cell through GntP or KguT, respectively (60, 61).…”
Section: Tobϩfum Susceptibility Requires Rponmentioning
confidence: 99%
“…From there, GLC either is directly transported across the inner membrane via the Glt transporter or is converted to gluconate or 2-ketogluconate, which is transported into the cell through GntP or KguT, respectively (60, 61). In the cytoplasm, GLC, gluconate, and 2-ketogluconate are then converted to 6-phosphogluconate, which is metabolized via the Entner-Doudoroff pathway to produce pyruvate and, ultimately, acetyl-CoA that can enter the tricarboxylic acid (TCA) cycle (60,61). Transcription of the genes involved in GLC uptake and metabolism is highly regulated by several transcription factors, including the repressors HexR, PtxS, GntR, and GltR as well as the activator PtxR (60,61).…”
Section: Tobϩfum Susceptibility Requires Rponmentioning
confidence: 99%
See 1 more Smart Citation